(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the impact of sensory motor training on balance and proprioception among postmenopausal obese women. Study Design: Interventional randomized clinical trial Place and Duration of Study: This study was conducted at the THQ hospital Faisalabad from September 2020 to March 2021 for a period of six months. Materials and Methods: A convenient sample of 40 postmenopausal obese women with age range 45-65 years were included after obtained informed consent and randomly divided into two equal groups. Group A (n=20) was received sensory motor training along with conventional therapy while group B (n=20) was only given conventional therapy. The interval of training was 6 weeks. Both groups were assessed by using functional reach test (FRT), time up and go test (TUG) and one leg stance test (OLS) at baseline and 6th week (pre- and post-estimation of postural strength). Values were obtained after intervention analyzed for any change using SPSS 25. Results: The results of this study found that SMT exhibited significant improvement in FRT score in Group A as compared with Group B at post-test, 11.35±1.34 vs 10.35±1.30 (p=0.022) respectively. TUG score significantly lower in Group A as compared with Group B, 9.00±1.52 vs 10.75±1.61 (p=0.001) respectively and proprioception OLS significantly increased with DO, 25.01±2.69 vs 22.46±2.27 (p=0.003), DC 6.54±.73 vs 5.99±.84 (p=0.034), OO 20.06±1.18 vs 17.61±1.28 (p=0.0001) respectively but non-significant increase in OLS with OC 3.49±.72 vs 3.09±.71 (p=0.089) respectively. Conclusion: This study concluded that sensory motor training show improvement in balance as well as proprioception. Static and dynamic balance indicated more improvement in sensory motor training when compared with conventional training while proprioception demonstrated almost similar outcomes for the both groups.